Research on on-line assembly and calibration system based on laser scanning and optical fiber sensor - Ding, Weijie; Li, Meixuan; Liang, Fang; Gao, Yan; Qin, Wei; Zhang, Hong (Frontiers in Physics, 2023)
In order to improve the degree of assembly automation, an online assembly calibration system is designed based on laser scanning and optical fiber sensors. The optical fiber sensing module is used to obtain the stress field information, and the laser scanning module is used to obtain the point cloud information of the assembly structure. The position offset caused by the stress field can be compensated to the 3D point cloud for improving the target reconstruction accuracy. It consists of laser scanning module, optical fiber sensor module, demodulator, data analysis module, etc. Analyzing the structural characteristics of the module, the stress field distribution of the module structure is obtained through simulation analysis, and an appropriate optical fiber sensor network layout is constructed. When the force is applied in different directions, the stress field distribution of the assembly structure is simulated and analyzed. The results show that the magnitude and direction of the residual stress have an impact on the distribution of the stress field. At the same time, the stress field diffusion degree had been also analyzed in different strength conditions. In the calibration test of FBG sensor, the functional relationship between wavelength variation and stress is about 0.0011 nm/N. In the assembly test, the stress test trends of different FBGs were obtained, and the relative error was concentrated between 4.0% and 9.0%, which had good stability. After correcting the position of the point cloud for optical fiber sensing data, the position deviation between the test point and the digital analog has been significantly reduced, with the average value decreasing from 2.953. to 0.095 mm. It has good applicability in factories with large interference of working environment, and can improve the application field of intelligent assembly.